Communicating climate change through place based engagement: methods, research, and applications to parks and protected area visitors - Davis, Shawn Kyle, author; Thompson, Jessica L., advisor; Donnelly, Maureen P., advisor; Vaske, Jerry J., committee member; Bruyere, Brett L., committee member; Champ, Joseph, committee member (Colorado State University. Libraries, 2014)
This research explored the connections between place attachment and resident perceptions of tourism. Aspects of place attachment such as place identity and place dependence were tested against tourism dependence for strength of correlation and relationship to perceived impacts of tourism. Survey data were collected from residents of eight communities in Colorado. The researcher hypothesized that there would exist a positive relationship between place dependence and place identity, as well as a negative relationship between place identity and tourism impacts. Results from this research show that place dependence has a direct effect on place identity (β = .61, p <.001). Place identity was found to have a significant effect on a variety of tourism impacts. Rapid advances in tablet technology and the increasing availability of electronic survey applications provide opportunities to streamline on-site human dimensions data col- lection. This article compares response rates and cost efficiencies of an iPad interface used for on-site survey administration to other types of human dimensions of wildlife survey administration response rates and expenses. Results also illustrate respondents' interface preference from a recent survey administered at National Wildlife Refuges and National Parks across the United States. Refuge and Park visitors enjoyed taking on-site surveys on iPads more than traditional paper surveys, and indicated a preference for taking future surveys on iPads instead of paper (t = 21.64, p < .001, η = .39); iPad survey administration was more cost efficient for large (over 1,350) survey samples, and garnered a higher than average response rate than online and mail surveys, but similar to average response rates for on-site intercept survey administration. In this paper we present and test a theoretical framework for place-based climate change engagement. The framework is based on principles from place attachment theory, place- based education, free-choice learning, and norm activation theory. The framework, which we empirically validate here, demonstrates the power of engaging citizens in action-based learning at physical, material places, which are also symbolic sites for inspiring political action and learning about climate change impacts. Research has shown that climate change will resonate with diverse audiences when: (1) it is situated in cultural values and beliefs, (2) it is meaningful to that audience, and (3) it empowers specific action. We use data collected at 16 national parks and wildlife refuges in the USA; all of which are experiencing the impacts of climate change and struggling to develop climate change communication and outreach activities for their visitors and local communities. Thus, this framework and the empirical validation presented are the result of triangulating quantitative survey data (n =4,181) and qualitative interviews (n =359) to argue for the unparalleled potential for America's parks and refuges to inspire civic engagement in climate change through place-based communication. People everywhere are defined in part by the places they live and the places they love. Climate change is a global challenge that threatens peoples' homes, work places and protected areas around the world. This paper explores the connection between the distance National Park visitors live from the Park and their perceived connection to that place as well as related influences on perception of climate change impacts. The researchers built upon Norton and Hannon's (1997) work hypothesizing that the closer visitors lived to the Park, the greater place attachment they would exhibit. Based on an on-site survey of visitors to Kenai Fjords National Park (KEFJ), visitors' place attachment and proximity to the Park were mapped using ArcGIS software. Results show that regardless of distance, the majority of visitors who took the survey reported that they have a strong attachment to KEFJ. This attachment positively correlated with visitor ability to see climate change impacts (r = .20, p < .001) and their desire to learn more about climate change (r = .26, p < .001) in the Park. This study shows that National Parks have the potential to educate a vast audience on the effects climate change will have to these iconic landscapes and how they help protect these places, regardless of where they live.
Keywords: survey; place attachment; tourism; climate change; communication